what expression is equivalent to (x-5)(2x+3)

1 answer

To find an expression equivalent to \((x - 5)(2x + 3)\), we can use the distributive property (also known as the FOIL method for binomials).

Let's expand the expression:

\[ (x - 5)(2x + 3) = x(2x) + x(3) - 5(2x) - 5(3) \]

Calculating each part, we get:

\[ = 2x^2 + 3x - 10x - 15 \]

Now, combine like terms:

\[ = 2x^2 + (3x - 10x) - 15 \] \[ = 2x^2 - 7x - 15 \]

So, the expression equivalent to \((x - 5)(2x + 3)\) is:

\[ \boxed{2x^2 - 7x - 15} \]